Transconjunctival correction of involutional entropion: A video demonstration - Neelam Pushker; B. Mounica; Sahil Agrawal (Indian Journal of Ophthalmology)
Background: Involution or aging is the most common cause of lower eyelid entropion (in-turning of eyelid margin) in the elderly population. Various pathomechanisms have been postulated for its occurrence. Aging leads to laxity of tissues and loss of muscle tone. Disinsertion/dehiscence of inferior retractors is considered as the major reason along with the loss of orbicularis muscle tone with or without over-riding of pre-septal fibers onto pretarsal fibers, and laxity of overall eyelid and/canthal tendons. The examination should focus on testing the above-mentioned predisposing factors. The clinical tests are as below. 1. Distraction/pinch test—This test is conducted to assess the overall eyelid laxity. The patient is asked to look in the primary gaze and the lower eyelid is pulled away from the globe. The distance between the pulled eyelid and the globe is measured in millimeters. The laxity is considered significant if the value is more than 6 to 8 mm, which varies according to the age of the patient. 2. Snapback test—This test is conducted to assess the tone of the orbicularis muscle. After doing the distraction test, leave the eyelid and check for its position in relation to the globe. If it snaps back immediately or follows a blink, then it is normal for an old patient. If on leaving the eyelid, it does not come in contact with the globe after blinking repeatedly, then the loss of tone is significant. 3. Medial canthal laxity—Pull the eyelid laterally and observe the shift of the puncta. Laxity is significant if the shift of puncta is 4 mm. 4. Lateral canthal laxity—Pull the eyelid medially and observe the shift of the lateral canthus. Laxity is significant if the shift of the lateral canthus is 4 mm. 5. Eyelid sagging/sclera show—The presence of the sclera due to eyelid sagging is suggestive of significant horizontal lid laxity. 6. Inferior retractor weakness—Inferior retractor weakness occurs because of its dehiscence or disinsertion. The presence of the following signs is suggestive of weakness, that is, higher eyelid resting in primary gaze, eyelid fails to retract on down gaze (normal excursion of the lower eyelid is 3–4 mm), increase in the depth of inferior fornix, and presence of white infratarsal band of retractors separated from the lower tarsal border by a pinkish orbicularis band. Surgical management of involutional entropion includes tackling the vertical component (inferior retractors reinsertion/plication or eyelid margin rotation surgery) with or without the horizontal component. Horizontal tightening (lateral tarsal strip procedure or full-thickness pentagon excision) is indicated in the presence of significant laxity of the overall eyelid and/or canthal laxity. Tackling both vertical and horizontal components gives the best long-term outcome. Purpose: To highlight important surgical steps of transconjunctival correction of left eye involutional entropion in a 70-year-old patient. Synopsis: The video 1 shows the correction of involution entropion by horizontal tightening (lateral tarsal strip procedure) and vertical tightening (advancement and reattachment of inferior retractors on the anterior surface of the tarsus) by conjunctival approach. The limitations of the procedure are mainly that it needs surgical expertise and excessive skin excision if needed cannot be conducted. In our experience, skin excision is not needed in unilateral cases to avoid asymmetry. The suture removal especially at the eyelid margin should be removed at 2–3 weeks to provide a strong attachment of inferior retractors with the tarsal surface. Highlights: Steps of transconjunctival correction of involutional entropion. Video Link: https://youtu.be/JVLi0PngKm4